2022
DOI: 10.1038/s41598-022-12438-4
|View full text |Cite
|
Sign up to set email alerts
|

OsSCL30 overexpression reduces the tolerance of rice seedlings to low temperature, drought and salt

Abstract: Rice is one of the main food crops for the world population. Various abiotic stresses, such as low temperature, drought, and high salinity, affect rice during the entire growth period, determining its yield and quality, and even leading to plant death. In this study, by constructing overexpression vectors D-163 + 1300:OsSCL30 and D-163 + 1300-AcGFP:OsSCL30-GFP, the mechanism of action of OsSCL30 in various abiotic stresses was explored. Bioinformatics analysis showed that OsSCL30 was located on the chromosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
0
11
1
Order By: Relevance
“…7 ), which was consistent with the previous study that OsRS33 gene knockout lines were more sensitive to salt stress compared with the wild type ( Butt et al, 2022 ). We found OsSCL30 was obviously and continuously suppressed by the cold treatment, and in fact, OsSCL30 was related to cold tolerance in rice, overexpression of OsSCL30 reduced the tolerance of rice seedlings to low temperature ( Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…7 ), which was consistent with the previous study that OsRS33 gene knockout lines were more sensitive to salt stress compared with the wild type ( Butt et al, 2022 ). We found OsSCL30 was obviously and continuously suppressed by the cold treatment, and in fact, OsSCL30 was related to cold tolerance in rice, overexpression of OsSCL30 reduced the tolerance of rice seedlings to low temperature ( Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 94%
“…By the experiments, OsSR45 was observed to co-express and physically interact with OsFKBP20-1b in the nucleus and cytoplasm in vivo ( Park et al, 2020 ). It has been proven experimentally that OsSCL30, which was the SR protein in rice, was visible only in the nucleus ( Zhang et al, 2022 ). The results indicated that different OsSR proteins together with their interaction proteins could function in different intracellular partitions.…”
Section: Resultsmentioning
confidence: 99%
“…Treatments used for stressed plants. In some cases, water shortage or dehydration was caused by not administering water for a certain time interval (e.g., Gontia-Mishra et al., 2016 ; Sheikh-Mohamadi et al., 2018 ; Vu et al., 2021 ), while in other cases, PEG was utilised to provide the drought stress (DS) (e.g., Vaishnav and Choudhary, 2019 ; Zhang et al., 2022 ). In two out of eight articles included in the meta-analysis for DREB2 in PGPR-inoculated plants ( Sarma and Saikia, 2014 ; Vaishnav and Choudhary, 2019 ), the authors decided to induce DS with PEG.…”
Section: Discussionmentioning
confidence: 99%
“…Rice transgenic plants exhibited greater phenotypic response, higher chlorophyll contents, proline contents, and yield than wild type ( Moin et al, 2021 ). Genetic engineering resulted in the transformation of genes that reduced salinity tolerance in rice, as revealed earlier by ( Zhang et al 2022 ), who showed that OsSCL30 reduced tolerance to salt stress in rice.…”
Section: Applications Of Genetic Engineering To Breed Salt-tolerant Ricementioning
confidence: 91%